Sequencing batch biofilm reactor : from support design to reactor operation - Matos, Maria F. (2011)
The aim of this work was to improve the overall understanding of sequencing batch biofilm reactors (SBBRs) from support selection (biofilm formation) to reactor operation (carbon and nitrogen removal). Supports manufactured with different materials and geometries were tested in 2.5 L SBBRs and it was observed that biofilm accumulation was favoured on the supports that presented a higher internal surface area. The geometry of the supports and the hydrodynamic conditions established in the SBBRs seemed to play a more important role in biofilm formation than the thermodynamic interaction, expressed as free energy of adhesion (G), between the support material and the biomass. The support that presented the highest biofilm accumulation per unit of surface area (DupUM) was used in a 28 L SBBR and it was observed that, along a typical SBBR cycle, time profiles of nitrogen compounds showed the typical behaviour of nitrification and denitrification reactions. During the fill phase (without aeration) acetate was simultaneously consumed in biomass growth and denitrification. Immediately after the beginning of the aeration phase (without influent addition), acetate was depleted from the liquid phase and stored as poly-ß-hydroxybutyrate that was later on used in the growth of biomass, owing to the high oxygen concentration in the reactor.